IMPROVING THE TECHNOLOGY OF BELORUSSIAN RAILWAY IN CONDITIONS OF ELECTRONIC DOCUMENTS USAGE - Kolos, M. M.; Gonchar, M. A. (Science and Transport Progress, 2016)
Purpose. The scientific paper highlights improving the technology of railway transport in the Republic of Belarus in conditions of electronic legally significant documents. Methodology. The study covered the collection of statistical data on the duration of separate technological operations performance, the evaluation of static data and the descriptive analysis of their characteristics. When assessing the effectiveness of the proposed measures we used methods of expert estimations, methods of evaluating the effectiveness of IT investments. Findings. Technology, hardware, software, organizational and other aspects of electronic legally significant documents used in freight and commercial work are determined. The work defines the most important directions of technology improvements at Belarusian Railway entities and their relations with shippers and consignees through the use of electronic legally significant documents. These directions are as follows: simplification of station commercial costs accounting, automation of technological operations, improving the interaction between the railway tracks and adjunction stations, simplification of transport planning and demand performance record, implementation of common information space for all participants of transportation process. The predictive estimate of efficiency for implementation of electronic legally significant documents in freight and commercial work of the Belarusian railway is calculated. Originality. This article presents a dual model of digital signature as a tool for the automatic fixation of technological operations or for specifying the time for its implementation, which allows converting a number of technological processes to a new level, helping to create a common information space of freight traffic. Practical value. The obtained results are used to form the list of the actions directed on perfection of railway transport technology in conditions of electronic legally significant documents, assessment of their significance and phasing of their implementation on Belarusian railway. The results of the project will allow: to reduce costs of shippers, consignees, railroads, to improve productivity, cost competitiveness of railway transportation and quality services, to create common information space and, as a consequence, to improve the quality of work with information flows and access to information for all participants of transportation process.